2018
DOI: 10.29333/ejmste/90988
|View full text |Cite
|
Sign up to set email alerts
|

The Didactic Contract to Interpret Some Statistical Evidence in Mathematics Standardized Assessment Tests

Abstract: In this study we analyse results of Italian standardized tests in mathematics integrating quantitative analysis based on the Rasch Model and didactical interpretation. We use specific graphs to analyse the trend of each answer as function of the students' math ability. This approach led us to focus on specific items in which a wrong answer results particularly popular among medium/high level students and analyse this particular trend with the lenses of math education theories. The study reveals that these phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…As already highlighted in earlier studies, data collection and analysis of the results of large-scale national and international assessment tests (see e.g. Ferretti, Giberti, Lemmo, 2018) can provide an opportunity to examine results through a very powerful quantitative lens and suggest (as in our case) specific issues about the macro-phenomena which emerge at a systematic level. In fact, these tests often reveal "phenomena" of students' behaviour when faced with various mathematics tasks and ultimately about their learning characteristics and processes, particularly regarding the dynamics and some causes of their difficulties.…”
Section: Resultsmentioning
confidence: 82%
“…As already highlighted in earlier studies, data collection and analysis of the results of large-scale national and international assessment tests (see e.g. Ferretti, Giberti, Lemmo, 2018) can provide an opportunity to examine results through a very powerful quantitative lens and suggest (as in our case) specific issues about the macro-phenomena which emerge at a systematic level. In fact, these tests often reveal "phenomena" of students' behaviour when faced with various mathematics tasks and ultimately about their learning characteristics and processes, particularly regarding the dynamics and some causes of their difficulties.…”
Section: Resultsmentioning
confidence: 82%
“…In a 1992 paper, Leder highlights possible causes of gender differences in mathematics as including variables related to the specific curricula of the discipline: the topics covered, the type of questions, the evaluation and teaching methods all play a fundamental role in the emergence of gender differences in mathematics. More recent studies have confirmed this hypothesis and have shown that, in addition to variables related to the curricula, also the teaching and assessment methods, didactic practices and socio-mathematical norms that are established in class have a significant influence on the gender gap in mathematics (Leder & Forgasz, 2008;OECD, 2016;Giberti, Zivelonghi & Bolondi, 2016;Bolondi, Cascella & Giberti, 2017;Bolondi, Branchetti & Giberti, 2018;Ferretti, Giberti & Lemmo, 2018).…”
Section: External Factorsmentioning
confidence: 91%
“…Valutazioni standardizzate di matematica: evidenze di difficoltà dalla scuola primaria alla scuola secondaria di secondo grado / Federica Ferretti DdM nomeni in livelli scolastici superiori (D'Amore, Fandiño Pinilla, Marazzani & Sarrazy, 2010;De Vleeschouwer & Gueudet, 2011) e in situazioni di valutazione su larga scala (Ferretti et al, 2018). Come già esplicitato, il focus dei quesiti oggetto di questo articolo riguarda la comprensione e la risoluzione di situazioni problematiche in sede di valutazione standardizzata.…”
Section: Prospettive Teoriche DI Indagineunclassified
“…Negli ultimi decenni sempre più ricerche hanno studiato fenomeni messi in luce dalle valutazioni standardizzate di matematica, indagandone peculiarità e caratteristiche con le lenti teoriche della didattica della matematica (De Lange, 2007;Sbaragli & Franchini, 2014;Ferretti & Bolondi, 2019). In particolare, nel contesto italiano, analisi qualitative e quantitative sui testi e sui risultati delle rilevazioni INVALSI hanno portato alcuni contributi significativi per la ricerca in didattica della matematica: non solo è stato possibile quantificare e misurare la portata di diversi fenomeni già studiati in letteratura inquadrabili con costrutti condivisi a livello internazionale -come ad esempio quello di contratto didattico (Ferretti, Giberti & Lemmo, 2018), ma dalle varie analisi sono emerse nuove evidenze e interpretazioni legate ai fenomeni stessi. Da quest'ultimo punto di vista, si è potuto mettere in relazione conoscenze, abilità e difficoltà degli studenti emerse durante la prova con il gender gap tra maschi e femmine (Bolondi, Bolondi, Cascella & Giberti, 2017); si sono anche studiati fenomeni nuovi come l'effetto "Età della Terra", che mette in evidenza come gli studenti tendenzialmente non ritengano plausibile che la risposta a un task matematico sia un dato esplicitamente presente nel testo del task, ma occorra "farci qualcosa"…”
unclassified